Hubungan Penggunaan Video Pembelajaran Di Masa Pandemi Covid-19 Terhadap Hasil Belajar Fiqih Siswa Kelas V MI Rare Muchtary Tahun Pelajaran 2020/2021 - Alinda, Lusiana; Rusmayani, Rusmayani; Arifin, Haris Nursyah (STAI Denpasar Bali, 2021)
Learning video is a type of media used in learning activities by involving the senses of sight and sense of hearing in an activity process. Messages and information that can be channeled through this media can be in the form of verbal and nonverbal messages that rely on sight and hearing. The objectives of this study are, 1) To find out the relationship between the use of learning videos during the COVID-19 pandemic to the learning outcomes of fiqh students in class V at MI Rare Muchtary for the 2020/2021 academic year, 2) To find out how much the contribution of the use of learning videos during the COVID-19 pandemic to the fiqh learning outcomes of fifth grade students at MI Rare Muchtary for the 2020/2021 academic year. This research is a quantitative correlational study. The sample used in this study were 49 students. then the data were analyzed using the product moment correlation formula. The results showed that the relationship between the use of instructional videos on the fiqh learning outcomes of fifth grade students at MI Rare Muchtary was moderate or adequate. With the value of the correlation coefficient (r_xy) is 0.648. This means that Ho is rejected and Ha is accepted, so that the relationship between the use of learning videos and learning outcomes of fiqh is positive. 2) the instructional video variable (X) has a simultaneous contribution of 36.2% to the variable of student fiqh learning outcomes for class V (Y) and the remaining 63.8% is influenced by other factors not examined in this study.